Algorytm korelacyjny do estymacji częstotliwości sygnału sinusoidalnego = An algorithm for the sinusoidal signal frequency estimation based on the autocorrelation function - Sienkowski, Sergiusz; Krajewski, Mariusz (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
In this paper a new, discrete-time algorithm for sinusoidal signal frequency estimation was presented. Such an algorithm was termed AMCAC (averaged modified covariance for autocorrelation).
Keywords: estymacja; algorytm korelacyjny; algorytm widmowy; algorytm podstawowy